(untitled) (REMUNOM, 2025)
Teaching Analytical Chemistry presents a challenge due to the complexity of the content and the perceived difficulty of students. Therefore, activities involving active methodologies in the teaching-learning context represent a significant transformation compared to the traditional educational model. Therefore, the objective of this work is to present a proposed educational game entitled "Complex Race," which serves as a support tool for teaching the nomenclature of complex compounds. The game was developed using accessible and low-cost materials, favoring its applicability in different educational contexts. Its structure consists of a board, cards containing multiple-choice or true/false questions, dice, and pawns representing the players. The results showed that the use of playfulness, as an active methodology, favors the teaching-learning process by enabling greater interaction among students and contributing to the retention of content. Therefore, it is concluded that educational games represent an effective strategy for developing a more dynamic, participatory, and motivating learning environment.